Self-management interventions to improve mobility after stroke: an integrative review. Issue 1 (2nd January 2023) - Sahely, Ahmad; Giles, Daniel; Sintler, Carron; Soundy, Andrew; Rosewilliam, Sheeba
Abstract: Purpose: To review the evidence around self-management interventions used to improve mobility post-stroke. Materials and methods: An integrative review was carried out. Eight databases were searched from 1992 to July 2021 using keywords based on the PICOS strategy. Two reviewers independently screened and extracted the relevant data. Quality of studies was assessed and a quantitatively led narrative synthesis of data, supported by qualitative evidence, was then conducted. Results: Twenty-four studies with 823 participants were reviewed. Self-management strategies such as patient education, providing information, goal setting, problem-solving, action planning, self-monitoring, and social support were integrated with rehabilitation therapy to improve mobility post-stroke. The reviewed studies showed improvements in functional mobility and walking ability, self-efficacy, participation in physical activity, and quality of life to various extents. Participants in qualitative studies considered the self-management interventions as a valuable addition to their therapy and perceived the improvement in their mobility following them. Conclusion: There is some evidence that self-management interventions help to improve mobility outcomes post-stroke. Heterogeneity of data in the studies made meta-analysis impossible. Most of the identified studies examined the feasibility and fidelity of the interventions and further research is warranted to examine the efficacy of these interventions to improve functional mobility post-stroke. Implications for rehabilitation: Self-management interventions can improve mobility-related outcomes, which are considered a priority goal for many stroke survivors. Survivors valued their participation in self-management integrated care programmes and linked that to the perceived improvement in their rehabilitation outcomes. Self-management interventions such as patient education, goal-setting, self-monitoring, and professionals/carers support have been found to improve mobility outcomes for stroke survivors. The outcomes that benefited to a slight extent using self-management were; functional mobility, walking ability (speed, distance, and endurance), and a number of steps per day.